Digital Oceans: Technology Proficiency and Educational Strategies for Citizenship - Silverstro Malara (Pensa MultiMedia, 2022)
This work inquiries the potential of the digital tool in teaching and the possibilities of gamification for teaching citizenship education in Italian schools. Starting from the Italian law n ° 92 of 2019, some limits of teaching in the field of citizenship are focused and strategies and methodologies are analyzed starting from the training of teachers in the development of digital skills, as indicated by the European Recommendations for the optimization of teaching and learning process and for the promotion of the interaction of fully inclusive educational contexts. Furthermore, as a strategy of choice, the suggestion that comes from gamification and the creation of innovative learning environments in highlighted, structured in accordance with internal motivation of the learner, stimulated by the interactive and collaborative modes of the video game and, often, forgotten by traditional teaching.